2006
DOI: 10.1016/j.medengphy.2005.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Sonomyography: Monitoring morphological changes of forearm muscles in actions with the feasibility for the control of powered prosthesis

Abstract: 1 Electromyography (EMG) has been widely used for the assessment of 2 musculoskeletal functions and the control of electrical prostheses, which make use of the 3 EMG signal generated by the contraction of the residual muscles. In spite of the successful 4 applications of EMG in different fields, it has some inherent limitations, such as the 5 difficulty to differentiate the actions of neighboring muscles and to collect signals from 6 deep muscles using the surface EMG. The majority of current EMG controlled pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
112
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 40 publications
3
112
0
Order By: Relevance
“…We studied the relationship between the thickness deformation SMG of the forearm extensor and wrist angle during wrist extensionflexion. We discovered qualitatively similar profiles between the SMG and the wrist angle, suggesting a high degree of correlation [7,[20][21][22]. Furthermore, we found that SMG profiles from amputees performing hypothetical wrist extension-flexion were similar to those from nondisabled subjects [20].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…We studied the relationship between the thickness deformation SMG of the forearm extensor and wrist angle during wrist extensionflexion. We discovered qualitatively similar profiles between the SMG and the wrist angle, suggesting a high degree of correlation [7,[20][21][22]. Furthermore, we found that SMG profiles from amputees performing hypothetical wrist extension-flexion were similar to those from nondisabled subjects [20].…”
Section: Introductionsupporting
confidence: 61%
“…We discovered qualitatively similar profiles between the SMG and the wrist angle, suggesting a high degree of correlation [7,[20][21][22]. Furthermore, we found that SMG profiles from amputees performing hypothetical wrist extension-flexion were similar to those from nondisabled subjects [20]. We then studied a prosthetic hand with 1 degree of freedom (DOF) that was controlled by the SMG signal obtained from nondisabled subjects offline [23].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Results were calculated from data obtained at 3 different wrist extension/flexion rates. contraction [41]. We found a good linear correlation (r = 0.91 ± 0.08) between the 1-D SMG signal and the corresponding wrist extension angle for the subjects tested (n = 9), demonstrating that the morphological changes of forearm muscles were significantly correlated to the motion of the related joint.…”
Section: Tablementioning
confidence: 53%
“…In a previous study, Zheng et al used sonomyography (SMG) with B-mode ultrasound images to describe realtime muscle thickness changes during contraction [41]. A system was developed to record and analyze ultrasound images, force, joint angle, and surface EMG simultaneously.…”
Section: Introductionmentioning
confidence: 99%